The Functional Role of Music in Communicating Death through/in YouTube Videos - Pentaris, Panagiotis; Yerosimou, Maria (Journal of Education Culture and Society, 2020)
Since the establishment of thanatology, the science of death, in the early 20th century, death has not only been considered a controversial subject, but it has also been regarded as a taboo topic. Various ways of communicating death have developed over the last few decades. With the advent of different mass and social media and their increasing impact on everyday life in the 21st century, death can now be communicated via a number of media platforms, such as television, radio, and online videos. This type of communication is underpinned by a series of dimensions, in particular music, that shape the conveyed message. Music has been extensively used in the dissemination of information in the wider media outlet. It is widely seen as a means of evoking emotions and of facilitating the process of assimilating information that is communicated via media. This paper seeks to discuss the functional role of music in communicating death in online video platforms. In particular, the example of the YouTube platform is used to identify the links between death, music and video platforms. This paper is part of a large-scale study on the functional role of music in communicating death through YouTube videos. It is suggested that music may serve as a link between media and death. The conclusions that are drawn in this paper are supported by the authors’ current and ongoing study and critical analysis of the deployment of music in the communication of death.